Incidence of cognitive and affective attitudes of consumers in the defense of a local brand - Otero-Gómez, María Cristina; Giraldo-Pérez, Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2020)
From marketing, this study explores the perceptions of consumers about the local brand La Catira Industria Láctea, located in the department of Meta, Colombia. It aims to analyze the cognitive and affective attitudes of the consumer in relation to the brand in order to establish the variable with the greatest impact on its defense. Data collection was carried out through 187 in-person and online surveys. Despite being a representative brand in the region, in the affective component 27.8% claim to love this brand, a value that did not exceed the percentages for the cognitive component, which shows that 66.4% claim that the products of the brand are of a very good quality. The results suggest that the perceived quality is the variable of the cognitive attitude that is most related to the defense of the brand. In addition, the weakness in the emotional bond is evidenced from the perspective of the consumer in relation to the brand studied.